2023
DOI: 10.3389/fvets.2023.1118604
|View full text |Cite
|
Sign up to set email alerts
|

Administration of melatonin prior to modified synchronization protocol improves the productive and reproductive efficiency of Chinese crossbred buffaloes in low breeding season

Abstract: IntroductionMelatonin is a neurohormone involving various biological processes, including restoration of cyclicity in animals with seasonal breeding patterns. The use of melatonin in different forms has gained broader acceptance in different species, particularly in summer anestrous buffaloes.ObjectivesThe objective of the current study was to evaluate the melatonin effect on the reproductive and productive performance of crossbred buffaloes during the low breeding season.MethodsSixty-five cyclic and reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Melatonin is involved in regulating seasonal animal reproduction ( 20 , 32 ). In an environment with varying light intensity, MT secretion in the body also varied considerably ( 33 ). In the present study, no notable differences were observed in MT concentration between groups on the day of CIDR insertion, the day of removal, and 48 h after CIDR removal.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is involved in regulating seasonal animal reproduction ( 20 , 32 ). In an environment with varying light intensity, MT secretion in the body also varied considerably ( 33 ). In the present study, no notable differences were observed in MT concentration between groups on the day of CIDR insertion, the day of removal, and 48 h after CIDR removal.…”
Section: Discussionmentioning
confidence: 99%